Energy efficiency of the vibratory device electromagnetic drive system - Cherno, O.O.; Monchenko, M.Yu. (Технічна електродинаміка, 2016)
The paper deals with the investigation of vibratory device electromagnetic drive system energy characteristics. By
means of numerical simulation of electromechanical processes, the values of the electromagnetic vibrator efficiency,
the frequency converter efficiency and the resulting efficiency of the drive system were calculated for the different values
of the output power and the current frequency. The optimal frequency, providing the maximum efficiency, was determined.
It was found, that an electromagnetic drive with an automatic control system provides a higher efficiency
than an unbalanced one. The theoretical results were confirmed by the results of the experiments. Стаття присвячена дослідженню енергетичних характеристик електромагнітного вібраційного привода. Шляхом чисельного
моделювання електромеханічних процесів були розраховані значення ККД електромагнітного вібратора, перетворювача
частоти і результуючого ККД привода для різних величин вихідної потужності та частоти струму. Визначено оптимальну
частоту, що забезпечує максимум ККД. Встановлено, що при автоматичному керуванні електромагнітний вібраційний
привод має більш високий ККД, ніж відцентровий. Проведено експериментальні дослідження, які підтверджують
отримані теоретичні результати. Статья посвящена исследованию энергетических характеристик электромагнитного вибрационного привода. Путем численного
моделирования электромеханических процессов рассчитаны значения КПД электромагнитного вибратора, преобразователя
частоты и результирующего КПД привода для разных величин выходной мощности и частоты тока. Определена
оптимальная частота, обеспечивающая максимум КПД. Установлено, что при автоматическом управлении электромагнитный
вибрационный привод имеет более высокий КПД, чем центробежный. Проведены экспериментальные исследования,
которые подтверждают полученные теоретические результаты.